A Survey on the State of Art Techniques for the Identification of Polyps for Colorectal Cancer - Devi, K. Gayathri; Makesh, C (International Journal of Computer Sciences and Engineering, 2025)
Computer Aided Diagnosis (CAD) is available for automatic detection of suspicious colorectal polyps in the CT images of the colon. These schemes help the radiologist to identify the location of the polyps in an efficient and accurate manner. A detailed survey was made on the different CAD scheme proposed by different authors for the detection of different categories of polyps. The different CAD schemes was implemented by incorporating some modification in the segmentation phase such as automatic colon segmentation or vary the identification of features in the feature extraction phase in the classical polyp detection system for the identification of polyps. Their performances were measured by two parameters sensitivity and specificity. Thus the ultimate aim of the authors was to improve the sensitivity and decrease the chance of missing sessile and flat polyps, with acceptable false-positive rates